1. Analisis Kebijakan Pengelolaan Perikanan Pesisir Provinsi Bengkulu - Syahrowi Syahrowi; Daniel R. Moninta, R. Dahuri, T. Kusumastanto, dan S. Budiharsono (JURNAL AGRIMANSION, 2007)
Abstract The aims of this research are(1) to assess economic contribution of Fisheries Management to the Product Domestic Regional Brutto (2) to analysis the new approach to support of coastal community income (3) to design policy of sustainable coastal fisheriesm management. The research has been conducted in Bengkulu Province by using survey methods of 578 respondents. The collected data have been analyzed by using Input-Output Table of Bengkulu Provinsi and Logical Framework Analysis (LFA). The result shows that the fisheries contribution to the economy of the province in 2002 was not significant considering the large area of its coastal zone. This indicated that the fishery sector, from upstream to the downstreams, has not been optimally managed. The backward and forward linkages values and sensitivity of capture fisheries were higher, compared to the culture fisheries. Expansion of brakishwater pond has a direct impact to mangrove degradation. Simulation shows that an increase of 30% in the Regional Expenditure Allocation for manpower development on trainings of the fishermans is the best effort to boost up the sector’s contribution to the growth of the economy in Bengkulu Province. However, the policy would also bring a risk of increasing environmental externality as a negative impact. The effort to increase the expansion of fishery processed product market through 80% increase in the market segment would result in most optimum impacts on the performance of the economy in the Province Abstrak Tujuan penelitian ini adalah (1) Mengkaji kontribusi ekonomi dari pengelolaan perikanan terhadap PDRB (2) Menganalisis pendekatan baru dalam menunjang peningkatan pendapatan masyarakat pesisir; (3) merancang kebijakan pengelolaan perikanan berkelanjutan. Penelitian telah dilakukan di Provinsi Bengkulu dengan menggunakan metoda survey terhadap 578 responden. Data yang terkumpul di analisis dengan menggunakan Tabel Input-Output Provinsi Bengkulu dan Logical Framework Analysis (LFA). Hasil penelitian menunjukkan bahwa kontribusi sektor perikanan dalam perekonomian pada tahun 2002 belum signifikan dibandingkan dengan potensinya. Hal ini mengindikasikan bahwa sektor perikanan dalam arti luas (dari hulu sampai hilir) belum dikelola secara optimal. Nilai Backward Linkages dan Forward Linkages sektor perikanan tangkap lebih besar dan derajat kepekaannya lebih tinggi dibandingkan dengan sektor perikanan budidaya. Hasil penelitian juga menunjukkan bahwa peningkatan alokasi belanja daerah untuk peningkatan SDM melalui pelatihan nelayan pengolah hasil perikanan sebesar 30 persen adalah upaya terbaik untuk meningkatkan besarnya kontribusi sektor perikanan terhadap pertumbuhan ekonomi, dengan resiko terjadinya peningkatan dampak negatifnya sebagai faktor eksternalitas lingkungan; sedangkan upaya meningkatkan perluasan pasar produk olahan perikanan dengan peningkatan pangsa pasar sebesar 80 persen, akan memberikan dampak yang paling optimal terhadap kinerja ekonomi.